Identification of Melanin in the Mantle of the Pacific Oyster Crassostrea gigas - Han, Yijing; Xie, Chaoyi; Fan, Nini; Song, Hongce; Wang, Xiaomei; Zheng, Yanxin; Zhang, Meiwei; Liu, Yaqiong; Huang, Baoyu; Wei, Lei; Wang, Xiaotong (Frontiers in Marine Science, 2022)
The Pacific oyster, Crassostrea gigas, is widely distributed and is substantially important to shellfish cultivation. Oysters with melanin-colored shells and soft parts are increasingly popular and are of high economic value. However, the distribution and synthesis of melanin in C. gigas remains unclear and there have been only few relevant studies on it. In this study, transmission electron microscopy (TEM) was used to observe melanin in the epidermis of dark mantle tissue. Melanocytes containing melanosomes were observed below the epidermis, suggesting the possibility of a gradual transfer of melanin from the mantle tissue to the epithelium. The frozen section technique and three melanin staining methods were used to confirm the presence of melanin. The results suggest that enzyme identification (DOPA) is a suitable method of melanin staining in the mantle tissues of C. gigas. This study preliminarily identified the existence of melanin in the mantle tissues of C. gigas and is a foundation for the study of melanin synthesis. Furthermore, it provides new insights into the mechanism of shell color formation.